Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
:Table of Content • The Impact of Public–Private Partnership on the Level of Medical Services Provided: An applied study of Saudi Arabian Airlines General Corporation and Fakeeh Medical Group Co-Prof. Vivian Mohammed Nasrulddin ,Ms. Amjad Matruh Almutaani ,Ms. Khulud Khalid Baobaid , Ms. Ruba Abdullah Alazwari,Ms. Elaf Mohammed Alotaibi , Ms. Shahad Abdullah Ayn Aldeen • The Impact of Project Management Practices on Institutional Excellence: An Applied Study of the Tarahum Committee for the Care of Prisoners in Riyadh Ms. Seham Hamdan Dasan Almakhlafi Alharbi • Comparative Analytical Study of Tax Legislation and its Impact on foreign Direct Investment Mr. Zain M. AlDahabi , Ms. Fatima A. Algazo , Dr. Amal Marshed Alanazi, Ms. Rula Yousef Hajjaj • The Application of the jurisprudential principle "No Harm and Reciprocating Harm" in the Saudi Criminal Procedure Law Ms. Shahad Abdulrahman Almazyed • The Nature and Causes of Corruption Crimes and the Importance of International Cooperation in Combating Them: An Analytical Study on the Qatari Experience Asst-Prof. Nashat Mfudi Maasfeh • The Impact of Prolonged Conflict on Yemen’s Agricultural Sector: A Longitudinal Analysis of Economic and Labor Dynamics (1961–2021) Mr. Muqbel Ahmed Muqbel Abdullah, Prof. Dr. Sertaç Dokuzlu • Measuring the Alignment Gap Between Organizational Strategic Plans and Vision 2030 Goals: An Analytical Study in Saudi Arabia Mr. Badr Saleh Al-Lehyani, Dr. Alok Tiwari Ramadhar Tiwari